Host metabolic benefits of prebiotic exopolysaccharides produced by Leuconostoc mesenteroides. (31st December 2023) - Miyamoto, Junki; Shimizu, Hidenori; Hisa, Keiko; Matsuzaki, Chiaki; Inuki, Shinsuke; Ando, Yuna; Nishida, Akari; Izumi, Ayano; Yamano, Mayu; Ushiroda, Chihiro; Irie, Junichiro; Katayama, Takane; et al.
ABSTRACT: Fermented foods demonstrate remarkable health benefits owing to probiotic bacteria or microproducts produced via bacterial fermentation. Fermented foods are produced by the fermentative action of several lactic acid bacteria, including Leuconostoc mesenteroides ; however, the exact mechanism of action of these foods remains unclear. Here, we observed that prebiotics associated with L. mesenteroides -produced exopolysaccharides (EPS) demonstrate substantial host metabolic benefits. L. mesenteroides -produced EPS is an indigestible α-glucan, and intake of the purified form of EPS improved glucose metabolism and energy homeostasis through EPS-derived gut microbial short-chain fatty acids, and changed gut microbial composition. Our findings reveal an important mechanism that accounts for the effects of diet, prebiotics, and probiotics on energy homeostasis and suggests an approach for preventing lifestyle-related diseases by targeting bacterial EPS.